Novel biotransformation of menthone by microbial strains and vermicompost microbial consortium - Gayan, Aparna; Sethi, Sonali; Prakash, Om; Pant, A.K. (Journal of Scientific Agriculture, 2017)
The aim of the study was to evaluate the ability of Trichoderma harzianum and Pseudomonas fluorescence and vermicompost microbial consortium to biotransform the monoterpene menthone. The different microbial transformation was carried out in different media including the control flask. Samples of different cultures were taken after every 24 hours, extracted with n-hexane and analysed by GC and GC-MS. The chemical structure of the bio transformed products were identified by GC and GC-MS. All the microbial strains led to the decomposition of menthone with time. The most valuable transformation was the production of menthol by vermicompost microbial strain. The obtained data indicated that vermicompost microbial consortium is a good biocatalyst to convert the ketonic group into hydroxyl group and showed the importance of various microbial strains in the biotransformation of the menthone.